KONJUNGSI DALAM BAHASA JAWA DIALEK SUROBOYOAN - Puspa Ruriana (Balai Bahasa Provinsi Papua, 2019)
Java Suroboyoan has unique dialect than Java Standard. The unique dialect makes Java Suroboyoan also has the unique in conjunction. The research is to makes description the several kinds of conjunctions in Java Suroboyoan and the function of conjunction in the daily activities. The method of the research is interview and the text book. The research is analyzed with descriptions and classification technique. The techniques classify the certain contruction elements sentences. The result of the research refers that conjunction in the Java Suroboyoan can be classified as 3 conjunction koordinatif and the 11 subordinatif conjunction.